The Ant Colony Optimization Algorithm Applied in Transport Logistics - Ostrowski, Krzysztof; Starzec, Mateusz; Starzec, Grażyna (Computer Science, 2024)
The Vehicle Routing Problem belongs to graph optimization and its goal is to find shortest routes visiting a given set of customers with additional constraints present. The article presents the ant colony optimization metaheuristic which solves vehicle routing problems and its real-life application in transport logistics (finding routes for delivery companies). The metaheuristic generated high-quality solutions (superior to compared methods). Our tool is flexible and enables us to solve various variants of routing problems so it is well suited to specific needs of transportation companies.